Unveiling the mechanism of construction workers' unsafe behaviors from an occupational stress perspective: A qualitative and quantitative examination of a stress–cognition–safety model. (January 2022) - Liang, Qi; Zhou, Zhiyuan; Ye, Gui; Shen, Liyin
Highlights: Explained why the unsafe behaviors of construction workers appear under stress. A Stress–Cognition–Safety model was developed for construction workers. Questionnaire survey and focus group studies were conducted to cross-validate the results. Abstract: The unsafe behavior of construction workers has been widely recognized as the key contributor to accidents in the construction industry. Studies claim that cognitive factors are the antecedents of safety behaviors. The construction industry is stressful. Although the interaction between stress and unsafe behaviors has been reported, it remains unclear how stress induces unsafe behaviors by construction workers. Current study aims to reveal the mechanism through which stress affects unsafe behavior using mixed research methods. Over five hundred quantitative data were collected from construction workers through questionnaire survey to develop structural equation models for the interactions between stress, cognition factors and safety behaviors. Five focus group studies for real projects were also conducted to collect qualitative data from over forty participants in order to empirically validate the results. The final Stress–Cognition–Safety model for construction workers confirmed that: 1) all five cognitive factors (safety awareness, safety knowledge, subjective norm, safety attitude, and perceived behavioral control) are influenced by at least one type of stress; 2) stress indirectly affects the unsafe behaviors of construction workers through three cognitive factors (safety awareness, subjective norm, and safety attitude); and 3) both physical and emotional stress directly induce unsafe behaviors. Practical recommendations, such as inclusion of stress management seminars into on-site safety training, regular safety inspection and effective communication, are made to address stress and safety issues. This study uncovers stress–cognition–safety interactions, enhancing current understanding of relevant knowledge and existing industrial practices regarding safety management and accident prevention in the stressful construction industry.